1998
DOI: 10.1086/515654
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception, Sexually Transmitted Diseases, and Risk of Heterosexual Transmission of Human Immunodeficiency Virus Type 1

Abstract: To examine associations between method of contraception, sexually transmitted diseases (STDs), and incident human immunodeficiency virus type 1 (HIV-1) infection, a prospective observational cohort study was done among female sex workers attending a municipal STD clinic in Mombasa, Kenya. Demographic and behavioral factors significantly associated with HIV-1 infection included type of workplace, condom use, and parity. In multivariate models, vulvitis, genital ulcer disease, vaginal discharge, and Candida vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
187
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(192 citation statements)
references
References 27 publications
(9 reference statements)
5
187
0
Order By: Relevance
“…[12][13][14][15] The relatively small effect size in our study was statistically significant in both the adjusted and unadjusted analyses because of the study's high statistical power (> 90%). However, the population-level impact of the use of hormonal contraceptives on HIV-1 infection rates was determined to be only 12% in adjusted analyses.…”
Section: Researchmentioning
confidence: 62%
See 2 more Smart Citations
“…[12][13][14][15] The relatively small effect size in our study was statistically significant in both the adjusted and unadjusted analyses because of the study's high statistical power (> 90%). However, the population-level impact of the use of hormonal contraceptives on HIV-1 infection rates was determined to be only 12% in adjusted analyses.…”
Section: Researchmentioning
confidence: 62%
“…[12][13][14][15][16][17] These findings were supported by a subsequent study by Heffron et al that provided new evidence suggesting an increased risk of contracting and transmitting HIV-1 infection associated with the use of hormonal contraceptives, particularly injectables. 18 Durban data from the MDP301 trial confirmed this.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Data from successive Demographic and Health Surveys (2) undertaken in nine subSaharan African countries were used: Burkina Faso (1992 and 1999), Cameroon (1991 and 1998), Ghana (1993 and1998), Kenya (1993 and1998), Madagascar (1992 and1997), Malawi (1992 and2000), Niger (1992 and 1998), Tanzania (1992Tanzania ( , 1996Tanzania ( and 1999, and Zambia (1992, 1996 and 2001). The percentages of women reporting a preceding birth interval of ≤ or > 24 months were tabulated by country and survey date with the percentages reporting current use of any modern reversible contraception, DMPA and the intrauterine device.…”
Section: Methodsmentioning
confidence: 99%
“…Hormonal contraception has been proven as one of the biological factors being linked to the acquisition of Human Immunodeficiency Virus (HIV) and other sexually transmitted infections (STIs). (5,6) In a study conducted among a cohort of female sex workers in Kenya, compared with those who don't practice contraception; those who rely on oral contraceptives (OCPs) are more likely to acquire chlamydia infection or vaginal candidiasis, but are less likely to acquire bacterial vaginosis. (6,7) The assumptions are that the cervical ectopy produced by oral contraceptives (OCPs) results in affected cervical -zone being more vulnerable to trauma and thus perhaps to HIV infection.…”
Section: Introductionmentioning
confidence: 99%